Two-Component System Genes in Sorghum bicolor: Genome-Wide Identification and Expression Profiling in Response to Environmental Stresses - Zameer, Roshan; Sadaqat, Muhammad; Fatima, Kinza; Fiaz, Sajid; Rasul, Sumaira; Zafar, Hadeqa; Qayyum, Abdul; Nashat, Naima; Raza, Ali; Shah, Adnan Noor; Batool, Riffat; Azeem, Farrukh; et al. (Frontiers in Genetics, 2021)
The two-component signal transduction system (TCS) acts in a variety of physiological processes in lower organisms and has emerged as a key signaling system in both prokaryotes and eukaryotes, including plants. TCS genes assist plants in processes such as stress resistance, cell division, nutrition signaling, leaf senescence, and chloroplast division. In plants, this system is composed of three types of proteins: response regulators (RRs), histidine kinases (HKs), and histidine phosphotransfer proteins (HPs). We aimed to study the Sorghum bicolor genome and identified 37 SbTCS genes consisting of 13 HKs, 5 HPs, and 19 RRs (3 type-A RRs, 7 type-B RRs, 2 type-C RRs, and 7 pseudo-RRs). The structural and phylogenetic comparison of the SbTCS members with their counterparts in Arabidopsis thaliana, Oryza sativa, Cicer arietinum, and Glycine max showed group-specific conservations and variations. Expansion of the gene family members is mostly a result of gene duplication, of both the tandem and segmental types. HKs and RRs were observed to be originated from segmental duplication, while some HPs originated from tandem duplication. The nuclear genome of S. bicolor contain 10 chromosomes and these SbTCS genes are randomly distributed on all the chromosomes. The promoter sequences of the SbTCS genes contain several abiotic stress-related cis-elements. RNA-seq and qRT-PCR-based expression analysis demonstrated most of the TCS genes were responsive to drought and salt stresses in leaves, which suggest their role in leaf development. This study lays a foundation for further functional study of TCS genes for stress tolerance and developmental improvement in S. bicolor.